1992
DOI: 10.1038/360672a0
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the β-amyloid precursor protein in familial Alzheimer's disease increases β-protein production

Abstract: Progressive cerebral deposition of the 39-43-amino-acid amyloid beta-protein (A beta) is an invariant feature of Alzheimer's disease which precedes symptoms of dementia by years or decades. The only specific molecular defects that cause Alzheimer's disease which have been identified so far are missense mutations in the gene encoding the beta-amyloid precursor protein (beta-APP) in certain families with an autosomal dominant form of the disease (familial Alzheimer's disease, or FAD). These mutations are located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
939
2
11

Year Published

1993
1993
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,674 publications
(992 citation statements)
references
References 17 publications
40
939
2
11
Order By: Relevance
“…Yield: 100%. 1 4-Chloro-N-(5-(2-cyanoethyl)-1,2,3,4-tetrahydronaphthalen-2-yl)benzenesulfonamide (7). A solution of 4-chloro-N-(5-(3-hydroxypropyl)-1,2,3,4-tetrahydronaphthalen-2-yl)benzene-sulfonamide (55 mg, 0.14 mmol) in ammonium hydroxide (1.5 mL) was added with iodine (110 mg, 0.43 mmol), and the resulting mixture was stirred at 60°C for 24 h. The reaction was then quenched at 0°C by addition of a saturated solution of sodium sulfite (2 mL).…”
Section: ■ Methodsmentioning
confidence: 99%
“…Yield: 100%. 1 4-Chloro-N-(5-(2-cyanoethyl)-1,2,3,4-tetrahydronaphthalen-2-yl)benzenesulfonamide (7). A solution of 4-chloro-N-(5-(3-hydroxypropyl)-1,2,3,4-tetrahydronaphthalen-2-yl)benzene-sulfonamide (55 mg, 0.14 mmol) in ammonium hydroxide (1.5 mL) was added with iodine (110 mg, 0.43 mmol), and the resulting mixture was stirred at 60°C for 24 h. The reaction was then quenched at 0°C by addition of a saturated solution of sodium sulfite (2 mL).…”
Section: ■ Methodsmentioning
confidence: 99%
“…This suggests that the physiological process of amyloid formation can be recapitulated in vitro and highlights Several studies using familial AD (fAD) mutations in animal models and cell culture experiments strongly support the notion that early intermediates in the fibrillization process (i.e., oligomers, including protofibrils) are the primary toxic Aβ species and have a central role in AD pathogenesis. This hypothesis is supported by (i) the lack of a clear correlation between fibrillar amyloid burden in AD patients and cognitive impairment 29,30 , whereas such a correlation has been reported for the soluble pool of Aβ (monomers and oligomers including protofibrils) and AD severity 31,32 ; (ii) the fact that autosomal dominant mutations in APP or its cleaving enzymes (presenilins), which favor increased production of Aβ42 and/or accumulation of protofibrils, are associated with the development of fAD [33][34][35][36] ; (iii) the indication that transgenic animals overexpressing fAD mutations in APP exhibit learning deficits and lower performance in memory tasks, compared with control animals, long before the appearance of amyloid plaques 37,38 ; (iv) the fact that intracerebral administration of soluble Aβ oligomers in live animals impairs cognitive performance and inhibits long-term potentiation (LTP), a cellular model of memory formation 19 , and induces widespread plaque pathology 39 ; and (v) the observation that treating cultured neurons with Aβ protofibrils results in impairment of ion channelss 40,41 , inhibition of LTP 42 , loss of synapses and cell death 14 . Finally, anti-Aβ antibodies specifically targeting oligomers, including protofibrils, block neurotoxicity in cultured neurons 43 and reverse behavioral deficits in mice 44 .…”
Section: Introductionmentioning
confidence: 99%
“…In studies where APP with the Swedish mutation was transfected into cultured cells, a greatly enhanced production of total A␤ was demonstrated [22,23]. These results have been extended to primary human cells where it was shown that media from fibroblasts with the Swedish APP mutation contained three times more total A␤ than media from control fibroblasts [24,25].…”
Section: Metabolic Effects Of App and Presenilin Mutationsmentioning
confidence: 81%